Tracing iron-fueled microbial carbon production within the hydrothermal plume at the Loihi Seamount - Bennett, S A; Hansman, R L; Sessions, A L; Nakamura, K; Edwards, K J (Geochimica et Cosmochimica Acta, 2011)
The Loihi hydrothermal plume provides an opportunity to investigate iron (Fe) oxidation and microbial processes in a system that is truly Fe dominated and distinct from mid-ocean ridge spreading centers. The lack of hydrogen sulfide within the Loihi hydrothermal fluids and the presence of an oxygen minimum zone at this submarine volcano's summit, results in a prolonged presence of reduced Fe within the dispersing non-buoyant plume. In this study, we have investigated the potential for microbial carbon fixation within the Loihi plume. We sampled for both particulate and dissolved organic carbon in hydrothermal fluids, microbial mats growing around vents, and the dispersing plume, and carried out stable carbon isotope analysis on the particulate fraction. The $δ$13C values of the microbial mats ranged from −23‰ to −28‰, and are distinct from those of deep-ocean particulate organic carbon (POC). The mats and hydrothermal fluids were also elevated in dissolved organic carbon (DOC) compared to background seawater. Within the hydrothermal plume, DOC and POC concentrations were elevated and the isotopic composition of POC within the plume suggests mixing between background seawater POC and a 13C-depleted hydrothermal component. The combination of both DOC and POC increasing in the dispersing plume that cannot solely be the result of entrainment and DOC adsorption, provides strong evidence for in-situ microbial productivity by chemolithoautotrophs, including a likelihood for iron-oxidizing microorganisms.
Keywords: ROV Jason (Remotely Operated Vehicle)